The Ion Permeability Induced in Thin Lipid Membranes by the Polyene Antibiotics Nystatin and Amphotericin B - Cass, Albert (The Rockefeller University Press, 1970)
Characteristics of nystatin and amphotericin B action on thin (<100 A) lipid membranes are: (a) micromolar amounts increase membrane conductance from 10(-8) to over 10(-2) Ω(-1) cm(-2); (b) such membranes are (non-ideally) anion selective and discriminate among anions on the basis of size; (c) membrane sterol is required for action; (d) antibiotic presence on both sides of membrane strongly favors action; (e) conductance is proportional to a large power of antibiotic concentration; (f) conductance decreases ∼10(4) times for a 10°C temperature rise; (g) kinetics of antibiotic action are also very temperature sensitive; (h) ion selectivity is pH independent between 3 and 10, but (i) activity is reversibly lost at high pH; (j) methyl ester derivatives are fully active; N-acetyl and N-succinyl derivatives are inactive; (k) current-voltage characteristic is nonlinear when membrane separates nonidentical salt solutions. These characteristics are contrasted with those of valinomycin. Observations (a)–(g) suggest that aggregates of polyene and sterol from opposite sides of the membrane interact to create aqueous pores; these pores are not static, but break up (melt) and reform continuously. Mechanism of anion selectivity is obscure. Observations (h)–(j) suggest—NH(3) (+) is important for activity; it is probably not responsible for selectivity, particularly since four polyene antibiotics, each containing two—NH(3) (+) groups, induce ideal cation selectivity. Possibly the many hydroxyl groups in nystatin and amphotericin B are responsible for anion selectivity. The effects of polyene antibiotics on thin lipid membranes are consistent with their action on biological membranes.